Physiological marker traits associated with submergence tolerance of lowland rice (Oryza Sativa) - SINGH, A K; SINGH, SANJAY; SINGH, ANURADHA; PRADHAN, S K; TYAGI, J P; SINGH, ALOK (The Indian Journal of Agricultural Sciences, 2011)
A field experiment was conducted during 2005–06 to elucidate the possible pre- and post-emergence traits associated with injury and submergence tolerance of lowland rice (Oryza sativa L.). Ten replicate pots with 5 plants in each pot were maintained per treatment under completely randomized design, respectively. The total protein content though was not much variable among varieties before submergence but decreased appreciably during submergence showing much lower values in intolerant varieties. A strong positive correlation between survival and protein content of leaves just after de-submergence was observed (R2= 0.90 for 5d) and (R2=0.93 for 10d) of complete submergence indicating a direct relationship of protein content with survival. Intolerant rice varieties accumulated 21 to 23 folds aldehyde on submergence against only 10 folds in tolerant ones showing a negative correlation (R2=0.9) between survival and aldehyde accumulation which might prejudice the submergence tolerance of rice. Activities of superoxide dismutase, catalase and peroxidase enhanced on submergence in all the varieties though the induction was more in tolerant varieties. ‘FR13A’ and ‘Vaidehi’ had 15 folds increase in superoxide dismutase activity against only 9 to 11 folds in ‘Mahsuri’ and ‘IR42’ respectively with 10 days complete submergence. These traits could possibly be looked into as markers for structuring submergence tolerant lowland rice.